A Critical Review on the Book Concise of the Approach to Scientific Research on Education and Anthropology - Abdolrazagh Rahmani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The research method is one of the fundamental courses that has been grown well in recent decades and has been well received; but unfortunately, despite the emphasis today on the research method and its proper application in various fields of science, we are witnessing less attention to this issue and its methods and principles in student research. Since most universities focus on research and research programs, they try to increase the student's awareness and knowledge of research methods in specialized fields. The book Concise of the Approach to Scientific Research on Education and Anthropology written by Dr Saif al-Islam has tried to explain the method of scientific research and the principles of dissertation writing to students. In the present study, this book has been reviewed and criticized with a descriptive-analytical method and has enumerated some of its advantages and shortcomings. Based on the findings of the current study, the author's ability to explain the content, coherence and order of topics, emphasizing the need to use a computer in scientific research, and observing writing marks are among the most important strengths of the book. However, lack of attention to in-text citations, lack of use of sources, and lack of comprehensiveness of some content and lack of explanation of the difference between methodology and research methods are the shortcomings of the book.